Routine monitoring of liver function tests in lung cancer resections – a necessary burden?. Issue 3 (August 2019) - Bradley, NA; Kennedy, ED; Asif, M
Background: Increased availability of routine investigations results in significant over-investigation, burdening patients with unnecessary tests as well as increasing cost. We aimed to identify the extent of monitoring of liver function tests in lung resections, and to ascertain whether any impact on clinical decision-making occurred. Methods: Cases were identified using theatre records coded as "lobectomy/bilobectomy" in the three-month period 20 June 2017 to 20 September 2017. Electronic records were used to collect patient data. Results: A total of 91 cases were included; 77 (85%) patients had 1 set of pre-operative LFTs, 12 (13%) patients had 2 sets, and 2 (2%) patients had 0 sets; 69 (76%) had normal LFTs pre-operatively; 298 sets of LFTs were measured post-operatively, with a median of 3 sets per patient; 61 (67%) patients had either normal or static LFTs post-operatively, 13 (14%) had isolated rise in GGT, 16 (17%) had derangement of ALT and AST, and 1 patient (1%) had deranged ALP. Altered clinical decision-making due to LFTs derangement was recorded in two cases (2%). Conclusion: Clinicians have an obligation to justify expense, and practise in a cost-effective manner. Our data suggest that the routine perioperative monitoring of LFTs in thoracic surgery does not give any clear benefit to patient care.